2010
DOI: 10.1002/micr.20812
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin sealant decreases postoperative drainage in immediate breast reconstruction by deep inferior epigastric perforator flap after mastectomy with axillary dissection

Abstract: This study introduce the interest of fibrin sealant to significantly decrease the postoperative drainage volume and duration in the thoracic area after immediate breast reconstruction by DIEP flap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
(39 reference statements)
0
5
0
1
Order By: Relevance
“…One study was excluded from the analysis due to its retrospective nature [ 13 ]. At the end of the selection process, 23/223 (10.3%) screened studies met the inclusion criteria [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Figure 1 shows the PRISMA flow chart outlining the process of evidence acquisition.…”
Section: Resultsmentioning
confidence: 99%
“…One study was excluded from the analysis due to its retrospective nature [ 13 ]. At the end of the selection process, 23/223 (10.3%) screened studies met the inclusion criteria [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Figure 1 shows the PRISMA flow chart outlining the process of evidence acquisition.…”
Section: Resultsmentioning
confidence: 99%
“…18 Similarly, Ali et al and Hivelin et al found that fibrin glue led to a significant reduction in the duration of drainage and earlier drain removal following reconstruction. 19,20 Dancey et al and Fang et al found a significant reduction in both drainage duration and seroma formation with fibrin glue and proposed that the additional cost of fibrin glue was worthwhile with regard to improved postoperative outcomes. 21,22 Bailey et al likewise showed a significant reduction in drainage duration, but the effect of fibrin glue on rate of seroma formation was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Benevento et al reported that fibrin sealants were able to reduce the output of serum from the axilla in patients who underwent axillary lymphadenectomy for breast cancer [ 9 ]. Fibrin sealants help to augment the final stage of coagulation when fibrinogen is converted into stable fibrinogen clot [ 18 ]. Fibrin formation not only controls bleeding, but also creates an adhesive barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin formation not only controls bleeding, but also creates an adhesive barrier. It could be expected that the fibrin sealant's hemostatic and adhesive properties could help reduce lymphatic drainage by sealing damaged lymphatic vessels via a less traumatic mechanism [ 18 ].…”
Section: Discussionmentioning
confidence: 99%